The Impact of Competition Intensity and Strategic Capabilities on Competitive Strategic Business Choices: The Case of Tunisian Manufacturing Industries - Zgarni, Asma; Lamia, Gharbi (International Review of Management and Marketing, 2019)
This article aims to show that competitive strategies can be traced back to both internal and external factors. In a sample of Tunisian companies, the concentration strategy, which is independent of marketing and market linkage capacities, is the most solicited faced to the competitive intensity. Cost dominance, which depends on managerial capacities, occupies the second position. Finally, differentiation is the least sought, but dependent on technological's and information technology's capabilities. Keywords: intensity of competition, strategic capabilities, competitive strategic choices, cost dominance, differentiation, concentration. JEL Classifications: L6, M1 DOI: https://doi.org/10.32479/irmm.6275